Relationship lending, firms' behaviour and credit risk: Evidence from the Czech Republic - Adam Geršl; Petr Jakubík (Charles University in Prague, Institute of Economic Studies (IES), 2010)
This paper presents the results of an analysis of data on individual bank loans of non-financial corporations in the Czech Republic taken from the CNB's Central Credit Register. It focuses on the question of how firms obtain financing from domestic banks. The results show that the vast majority of non-financial corporations use the services of just one relationship lender. Small and young firms in technology- and knowledge-intensive industries tend to concentrate their credit needs in a single bank, whereas less creditworthy firms and firms in cyclical industries tend to borrow from more than one bank. The analysis also reveals different behaviour of firms towards financing banks in case of multiple lenders. Finally, the paper shows that the level of credit risk at bank level decreases in line with the extent to which firms applying single relationship lending occur in the bank's portfolio.
Keywords: G21; G32; 330; relationship banking; credit risk; Bankgeschäft; Kreditgeschäft; Hausbank; Kreditrisiko; Tschechische Republik